Unidirectional Photon Coupling Using Asymmetric Diamond Emitters with Enhanced Spontaneous Emission. Issue 7 (21st May 2022) - Murmu, Satyajit; Kumar, Avijit; Jha, Rajan
Abstract: The directional coupling of single photon emission from nitrogen vacancy (NV – ) emitters to optical systems for various applications requires a suitable interface between NV – emitters and optical waveguides. Unidirectional coupling of photons may have significant importance in next generation quantum technology such as quantum and complex optical networks, quantum communication, and multi‐scale quantum photonics devices including quantum non‐linearity and quantum metrology. Here, a hybrid asymmetric structure of elliptically faceted (ELFA) diamond nanowire with Bragg grating (BG) containing negatively charged NV – center for efficient and unidirectional optical coupling to optical nanowire (waveguide) is proposed. The calculations indicate that the structure can provide coupling efficiency of ≈90% toward the elliptically facet direction and ≈1% in the opposite direction. Further, Purcell factor is enhanced due to the augmented electric field intensity in the ELFA structure. This structure is significantly robust against imperfect placement and rotational alignment of dipole from its intended position. Abstract : This article describes photon coupling in hybrid structure containing asymmetric elliptically faceted (ELFA) diamond nanowire with and without Bragg grating (BG) integrated with optical nanowire. Emission from the diamond nanowire with (without) BG leads to unidirectional coupling efficiency of 90% (57%) toward elliptically facet direction. The field intensity profile around dipole in transmission (launched‐light) leads to higher Purcell factor.